A model for steady state stage III creep regime at low-high stress/temperature range - Nicola Bonora; Luca Esposito (Fracture and Structural Integrity)
Although diffusional flow creep is often considered out of practical engineering applications, the need for a model capable to account for the resulting action of both diffusional and dislocation type creep is justified by the increasing demands of reliable creep design for very long lives (exceeding 100.000h), high stress-low temperatures and high temperature-low stress regimes. In this paper, a creep model formulation, in which the change of the creep mechanism has been accounted for through an explicit dependence of the creep exponent n on stress and temperature, has been proposed. An application example of the proposed approach to high purity aluminum is given.